Customer Loyalty in FMCG Sector of Pakistan - Zaman, Khansa; ., Asma Arshad; ., Aqeel Shahzad (Information Management and Business Review, 2012)
The purpose of this study is to find an empirical relationship of proposed variables and to find the impact of customer satisfaction, trust, and corporate reputation on customer loyalty. This study attempts to contribute to the knowledge how FMCG companies of Pakistan can retain their customers by making them loyal through satisfaction, trust, and corporate reputation. A theoretical framework is proposed to suggest links among variables. The sample size selected for research constitutes 200 respondents, and these respondents belong to the cities of Rawalpindi and Islamabad, Pakistan. Multiple regression and correlation coefficient was used to examine hypothesized relationship. Regression analysis reveals that customer satisfaction, trust, and corporate reputation bring 79.0% change in customer loyalty. There is a strong positive yet significant relationship of trust and customer loyalty. Customer satisfaction & corporate image also posit a positive and significant impact on customer loyalty. The results indicate that FMCG companies in Pakistan should pay more attention toward the reputation of their company, satisfaction of their customers, and trust in order to build loyalty of customers. Generalizability and time constraint are the limitations of the study.